The Matrix of Derivative Criminal Liability - Hallevy, Gabriel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Derivative criminal liability includes inchoate offenses (criminal attempt, conspiracy, preparatory offenses, etc.), complicity (joint perpetration, perpetration through another, incitement, solicitation, accessoryship, etc.), organized crime, natural and probable consequences liability, post-crime aid, enterprise liability, terrorism and terrorist infrastructure, and many more forms of criminal liability, clearly making it a major pillar of modern criminal law. Although derivative criminal liability affects countries worldwide, there is still no general legal theory that covers this issue. The objective of the present book is to develop a comprehensive, general, legally sophisticated, and at the same time practical theory of derivative criminal liability. The book emphasizes the practicality of the theory to enable courts, lawyers, legislators, attorneys, students, and academics to apply it in their daily professional occupations.
The Principle of Personal Liability and Its Applicability to Derivative Criminal Liability -- Typology of Derivative Criminal Liability -- The Matrix of Derivative Criminal Liability: General Principles -- The Factual Element Requirement -- The Mental Element Requirement -- Boundaries of Derivative Criminal Liability -- Conclusion.
Keywords: Law; Criminology; Law; International Criminal Law; Criminology & Criminal Justice; Theories of Law, Philosophy of Law, Legal History; Private International Law, International & Foreign Law, Comparative Law